APLIKASI KURVA PERTUMBUHAN LATEN PADA DATA INDEKS PEMBANGUNAN GENDER DI JAWA TIMUR - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; I Gede Heprin Prayasta; Ida Ayu Candrawati; Nurhidayati Nurhidayati; Sigit Budiantono (LPPM Universitas Bina Bangsa, 2024)
In the context of human development, gender equality is considered an important basic dimension, and one way to measure it is with the achievement of the Gender Development Index (GDI). East Java is one of the provinces in Indonesia whose GDI value consistently increases from year to year. This study aims to model GDI growth with latent growth models. The data used was sourced from the Statistics Indonesia of East Java with the research unit of regency in East Java in the 2017-2021 period. The results obtained were sustainable GDI growth in East Java City District. Modelling in latent growth curve method showed that the variation in growth was explained by 99 percent over the 5-year study period. Implementation in this study requires comprehensive and targeted efforts from policy makers in maintaining and increasing IPG growth in East Java